Anatomy and histology of the alimentary canal of larvae and adults of Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae). (January 2021) - Dantas, Priscylla Costa; Serrão, José Eduardo; Santos, Helen Cristina Pinto; Carvalho, Geraldo Andrade
Abstract: The larvae of the lacewing Chrysoperla externa are important predators with the potential to be used in the biological control in agriculture. Although some studies provide important data on the gut morphology in lacewings, they are limited to few species. This study describes the anatomy and histology of the alimentary canal in the predatory larvae and herbivorous adult of C. externa . In larvae, the crop is the larger part of the foregut and it is connected to the midgut by the stomodeal valve. The midgut is an enlarged sac-like organ. At the mid-hindgut transition, there are eight Malpighian tubules. The hindgut is a non-functional vestigial region in the larvae. In adults, the crop has a diverticulum associated with large tracheal trunks, a conic proventriculus with sclerotized lips followed by an elongated tubular midgut. Histological analyses of larval and adult midgut show the presence of a single-layered epithelium with columnar cells with well-developed brush border, nests of regenerative cells, and a peritrophic matrix lining the midgut lumen. The hindgut in adults has an epithelium with cubic cells lined by a thin cuticular intima and rectal pads in the rectum. These data are discussed in comparison with the digestive tract in other Chrysopidae. Highlights: The alimentary canal of larvae and adults of predatory insect is described. Larvae and adults have different anatomical features of the alimentary canal. Data on morphology of the alimentary canal are important for mass rearing of this insect.